Evaluation of emergency nurses’ knowledge of medical response in nuclear and radiological emergencies : a cross-sectional study - Nasser Shubayr (BMC Nursing)
Abstract Background Evaluating emergency room nurses’ knowledge of radiation protection, health effects, and decontamination procedures is crucial for preparedness in nuclear and radiological emergencies. This study aims to evaluate the level of knowledge among emergency nurses in Saudi Arabia regarding medical responses to nuclear and radiological emergencies. Methods A multicenter cross-sectional study was conducted via a self-structured questionnaire with 15 true‒false questions divided into three domains, namely, radiation protection measures, radiation health effects, and decontamination procedures, each with five items and a possible score of 1 point per correct answer. The collected data were analyzed via descriptive and inferential statistics. The study followed the STROBE checklist for methodological rigor. Results A total of 594 emergency nurses participated in this study, with the majority being young (64.50% aged ≤ 30), female (68.69%), bachelor’s degree-holding (67.68%), single (63.64%), having ≤ 4 years of experience (56.06%), working in public health facilities (88.89%), and lacking training in medical response (85.35%). The mean knowledge scores for participants were highest for radiation exposure effects (3.27 ± 0.91), followed by radiation protective measures (2.32 ± 0.99), and lowest for decontamination procedures (1.46 ± 1.07). Overall knowledge was measured at a mean score of 7.06 ± 1.68, with 97.47% of the nurses categorized as having poor knowledge level. Nurses in private hospitals scored higher (7.77 ± 1.82) than those in public hospitals (6.97 ± 1.65) on overall mean knowledge (P = 0.034). Concerning findings include emergency nurses’ misconceptions about the protection provided by dense materials, the effectiveness of increasing distance from a radiation source, and prioritizing decontamination of victims over life-saving measures. Additionally, they were unaware of the immediate symptoms following radiation exposure and misunderstood that the primary threat in a radioactive bomb event is the explosion rather than the radiation itself. Conclusion This study revealed poor knowledge among emergency nurses regarding medical responses to radiation emergencies and highlighted the critical need for enhanced and standardized training in radiation emergency preparedness among nurses. The gaps in knowledge identified in this study could significantly impact the effectiveness of healthcare responses in radiation emergency scenarios. Therefore, targeted educational interventions and policy changes are recommended to address these shortcomings.